Measuring Autocratization - Lott, Lars; Croissant, Aurel (Routledge Handbook of Autocratization, 2024)
This chapter provides a systematic review of the research on measuring autocratization, including its sub-dimensions such as democratic recession and autocratic hardening. We begin by outlining the debate on how to measure democracy, distinguishing between objective and subjective measures. We argue that subjective data should be used to measure autocratization processes, as “more objective” measures of democracy often lack conceptual clarity and theoretical embeddedness. We then differentiate between binary and continuous data on democracy, and illustrate how autocratization can be measured with these two types of data. Additionally, we differentiate between different approaches, namely the delta approach and the episode approach, for embedding change over time to measure autocratization with continuous democracy data. All of these approaches require the use of theoretically informed thresholds to identify autocratization. By providing a comprehensive overview of the literature and outlining a systematic approach for measuring autocratization, this chapter contributes to a better understanding of the process of autocratization and its sub-dimensions.<br